An Afghan diary : Zahir Shah to Taliban - Dixit, J. N. (Jyotindra Nath), 1936-2005. (New Delhi : Konark Publishers, 2000)
Reproduction of authors political diary on the political developments from 1982 to 1985 in Afghanistan.
Includes index.
Keywords: Dixit, J. N. -- 1936-2005 -- Diaries; Foreign ministers -- India -- Diaries; Afghanistan -- Politics and government -- 1973-; Afghanistan -- Foreign relations -- India; India -- Foreign relations -- Afghanistan